REINTERPRETASI SANKSI PIDANA ISLAM (STUDI TERHADAP PEMIKIRAN PROF. KH. IBRAHIM HOSEN, LML) - Andiko, Toha (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
Reinterpretation of Islamic Penal Punishment: A Study on Prof. K.H. Ibrahim Hosen, LML’s thought.Islamic penal punishment that is related to the qishas and hudûd is often considered as violating of human rightsand intimidation so that there are many rejections in its application. This is reinforced by the opinion of mostMoslem scholars who consider the implementation of Islamic penal provision through textual understanding asa symbol of the implementation of Islamic law as a whole. In this context, Ibrahim Hosen as the expert of Ushulal-Fiqh (Islamic Legal Theory) and comparative Islamic legal (Fiqh al-Muqâran) in Indonesia tried to neutralize therigid understanding by using the types of crime and the reinterpretation of punishment through understandingof the texts contextually by using ijtihad istislahi (independent reasoning of public interest) and refers to thepurpose of its application that prefers to the function of zawajir than the other. Therefore, it is expected that theIslamic penal law can be accepted theoretically and practically